Association of Serum Biomarkers with C-X-C Motif Chemokine Receptor 3 Gene Polymorphism and Severity of Coronavirus-2019 Infection - Usha Sachidananda Adiga; Sachidananda Narasimha Adiga; Tirthal Rathnakar Rai (Biomedical and Biotechnology Research Journal, 2024)
Background: Polymorphisms in the C-X-C motif chemokine receptor 3 (CXCR3) gene may impact the immune system’s reaction to infections such as coronavirus disease-19 (COVID-19). Nevertheless, a detailed analysis of the precise influence of CXCR3 gene polymorphisms on COVID-19 has not yet been conducted. This study aims to determine the genotype distribution of three specific CXCR3 gene polymorphisms (rs770806154, rs776323716, and rs778526136) and their potential association with the severity of COVID-19. Methods: One hundred COVID-19 patients were enrolled after the study protocol was approved by institutional ethical clearance. Selection of single-nucleotide polymorphisms was based on the bioinformatics analysis; CXCR-3 receptor (rs770806154, rs776323716, and rs778526136) polymorphism was analyzed by sequencing. D-dimer, ferritin, and erythrocyte sedimentation rate were estimated by Cobas C-311. Chi-square analysis was used to find the association of gene polymorphisms with the severity of infection and clinical parameters. P <0.05 was considered statistically significant. Results: Significant deviations from Hardy–Weinberg equilibrium for all three gene variations were observed and a significant association of CXCR3 (rs778526136) gene polymorphism with D-dimer levels and COVID-19 severity was observed. However, the other genotypes had no significant association with disease severity. Conclusion: A significant association was observed between the severity of COVID-19 and CXCR3 (rs778526136 variant) gene polymorphisms. The lower severity of COVID-19 is linked to the rs778526136 mutant genotype, indicating a protective effect. Hence, emphasizing the possibility that genetic factors could affect the course of COVID-19 and genetic screening could thus help in controlling COVID-19 severity.